Analisis Framing Pemberitaan mediaindonesia.com dan kompas.com Terhadap Berita Puan Maharani Sebagai Bakal Calon Presiden 2024 - Siti Hajiza; Puji Santoso (Universitas Muhammadiyah Sumatera Utara, 2022)
This study aims to find out how two online media, www.mediaindonesia.com and www.kompas.com, framed the news coverage of Puan Maharani's image as a presidential candidate for the Republic of Indonesia in 2024. This study used a qualitative method using a framing analysis knife by Robert Entman's model. The framing analysis method used is to analyze the 10 news items in the two online media about the imaging of Puan Maharani as a presidential candidate for 2024. The measurement is carried out by defining problem models, diagnosing problems, making moral judgments, and treatment recommendations. The results of the study concluded that the news coverage of two online media, namely mediaindonesia.com and kompas.com about the news of Puan Maharani as a presidential candidate for the period 2024-2029 using Robert Entmant's framing analysis model, is known that the online media are www.kompas.com and www.mediaindonesia.com jointly conduct moral judgments (moral policies) by criticizing the use of common sense (make sense) when there are state officials like Puan Maharani who have ambitions to become the head of the state (president) in an atmosphere of concern for the people.